The Antigerminative Activity of Twenty-Seven Monoterpenes - De Martino, Laura; Mancini, Emilia; Rolim de Almeida, Luiz Fernando [UNESP]; De Feo, Vincenzo (Mdpi Ag, 2010)
Monoterpenes, the main constituents of essential oils, are known for their many biological activities. The present work studied the potential biological activity of twenty-seven monoterpenes, including monoterpene hydrocarbons and oxygenated ones, against seed germination and subsequent primary radicle growth of Raphanus sativus L. (radish) and Lepidium sativum L. (garden cress), under laboratory conditions. The compounds, belonging to different chemical classes, showed different potency in affecting both parameters evaluated. The assayed compounds demonstrated a good inhibitory activity in a dose-dependent way. In general, radish seed is more sensitive than garden cress and its germination appeares more inhibited by alcohols; at the highest concentration tested, the more active substances were geraniol, borneol, (+/-)-beta-citronellol and alpha-terpineol. Geraniol and carvone inhibited, in a significant way, the germination of garden cress, at the highest concentration tested. Radicle elongation of two test species was inhibited mainly by alcohols and ketones. Carvone inhibited the radicle elongation of both seeds, at almost all concentrations assayed, while 1,8-cineole inhibited their radicle elongation at the lowest concentrations (10(-5) M, 10(-6) M).
Keywords: monoterpenes; germination; radicle elongation; phytotoxicity